THE IMPACT OF BIG DATA ON THE OPTIMISATION OF MARKETING CAMPAIGNS: A LITERATURE REVIEW - Loso Judijanto (CV. ADIBA AISHA AMIRA, 2025)
This literature review explores the impact of big data in optimising marketing campaigns. Big data has revolutionised the way companies collect, analyse and utilise data to develop more effective marketing strategies. With the ability to process large amounts of data from various sources, big data introduces new methods for understanding consumer behaviour and preferences. This study identifies that the application of big data enables higher personalisation in marketing campaigns, increasing consumer engagement and conversion through relevant and targeted messages. In addition, the measurement and evaluation of campaign effectiveness becomes more accurate and real-time, enabling quick and precise adjustments to marketing strategies. Overall, the use of big data in marketing not only provides strategic advantages for companies, but also increases competitiveness in dynamic and competitive markets.